NEEDS ANALYSIS FOR DEVELOPING AN AUGMENTED REALITY-BASED ECOSYSTEM MODULE ASSISTED BY ASSEMBLR APPLICATION FOR GRADE V ELEMENTARY SCHOOL - Ulfah, Tsaqifa Taqiyya (UIN Sunan Kalijaga Yogyakarta, 2022)
Technology is developing very rapidly and impacts all aspects, one of which is education. Based on these conditions, teachers must be able to conduct learning that is adaptive to technology. One of the utilization of technology in learning is learning media. IT-based learning media is very popular with students because it looks attractive and facilitates student understanding when learning. However, based on the facts, using technology media is not optimal. Based on these problems, this study aims to analyze the need for AR-based module development assisted by the Assemblr application. Researchers use qualitative methods. The data accumulation used by researchers is interviews, observations, and filling out online questionnaires. The results showed that 1) Students are already proficient in using cell phones and depend on gadgets. 2) Students like science learning on ecosystem material. 3) Students like colorful media such as videos. 4) The school needs to have its module. 5) Teachers and students must become more familiar with Augmented Reality technology. 6) Learning media that is often used package books and PPT so that it is less varied.